Enhancing the corporate visual identity of Universiti Putra Malaysia - Fu, Chew Xiang (2011)
Traditionally, Corporate Visual Identity have subscribed to the belief that it distinguishes an organization from its competitors by allowing its customers to understand, to differentiate and remember the organization. Developing a distinctive University Corporate Visual Identity is the way to be one of the most outstanding universities and to ensure the abilities and qualities of the university. Recent developments in Corporate Visual Identity have heightened the need for university in projecting implementation plan on the corporate identity guidelines in Malaysia universities. Few researchers have already drawn attention to the paradox in Corporate Visual Identity for universities in United Kingdom. The issue has grown in as importance in the light of recent university Corporate Visual Identity, however, far too little attention has been focused to the Corporate Visual Identity in Malaysia universities. Throughout this paper, the term CVI will be used to refer to Corporate Visual Identity. Research has consistently shown that Malaysia Universities may not have attained an adequate understanding of CVI. The objectives of this research are to determine the significance of corporate identity design in Malaysia of higher learning institutions, to establish design criteria for effective university CVI in Malaysia, also, to improve current CVI for Universiti Putra Malaysia. This study explores the relationship between universities in Malaysia and its CVI based on a multi-method study including literature search, and questionnaires survey from selected universities in Peninsular Malaysia, interviews to the Public Relation Offices of selected universities and visual search from the internet were employed. The response of the questionnaire sample is assumed to represent the general public to compares the application, perceived the importance of visual preferences to support the consistency of university CVI. The respondents were selected from local universities in Peninsular Malaysia. This study is expected to produce standard CVI guidelines developed from the analysis results in local context. It will be used for improving and optimizing the existing CVI guidelines for universities in Malaysia based on local context. Accordingly, it contributes towards the potential recommendations of CVI guidelines for Universiti Putra Malaysia. Hence, CVI must be considered a useful tool in university to achieve positive image and effective branding. Data revealed criteria of the main elements in university CVI which were categorized as follow: corporate logo, stationeries, publications, livery design, signage, and website applications. In explaining the above, the above states are viewed in terms of a university CVI which reflects the Malaysia university CVI context. The results showed greater consistency in the University CVI of brand establishing, in accordance with the amount of effort these universities put into CVI management. It will also be helpful to professionals who deal with integrated communication.